Acupuncture for allergic rhinitis: protocol for a systematic review and network meta-analysis - Chen, YanNi; Song, ChenFei; Wang, JiaQin; Han, XinMin (Frontiers in Allergy, 2024)
IntroductionAllergic rhinitis (AR) is a widespread inflammatory disorder of the nasal mucosa affecting millions globally. The increasing prevalence of AR underscores the need for effective treatment modalities. Acupuncture has been identified as a potential non-pharmacological intervention for AR due to its effects on autonomic nerve functions and neuroendocrine and immune networks. However, a comprehensive evaluation of different acupuncture techniques through high-quality, evidence-based research is still needed.Methods and analysisRandomised controlled trials of different acupuncture-related therapies for postmenopausal osteoporosis will be searched in the following databases from 1 January 2002 to 31 December 2022, including PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, VIP Database, Wanfang Database and China Biomedical Literature Database. Overall, clinical efficacy rate, bone mineral density and a Visual Analogue Scale score are used as the primary outcome indicators. In addition, the secondary outcome indicator is adverse reactions. Meanwhile, Stata (V.14.0) and RevMan (V.5.4) will be used to conduct the network meta-analysis. If the data are permissible and feasible, we will also perform meta-regression and subgroup analyses to address the underlying causes of data inconsistency and heterogeneity in the statistical analyses. To improve the credibility of this network meta-analysis, we will evaluate the quality of evidence in this research according to the GRADE assessment. Prospero Registration Number: identifier (CRD 42024579713).